Description of the COVID-19 epidemiology in Malaysia - Md Nadzri, Mohamad Nadzmi; Md Zamri, Ahmed Syahmi Syafiq; Singh, Sarbhan; Sumarni, Mohd Ghazali; Lai, Chee Herng; Tan, Cia Vei; Aris, Tahir; Mohd Ibrahim, Hishamshah; Gill, Balvinder Singh; Mohd Ghazali, Nur’Ain; Md Iderus, Nuur Hafizah; Lim, Mei Cheng; et al. (Frontiers in Public Health, 2024)
Introduction: Since the COVID-19 pandemic began, it has spread rapidly across the world and has resulted in recurrent outbreaks. This study aims to describe the COVID-19 epidemiology in terms of COVID-19 cases, deaths, ICU admissions, ventilator requirements, testing, incidence rate, death rate, case fatality rate (CFR) and test positivity rate for each outbreak from the beginning of the pandemic in 2020 till endemicity of COVID-19 in 2022 in Malaysia. Methods: Data was sourced from the GitHub repository and the Ministry of Health's official COVID-19 website. The study period was from the beginning of the outbreak in Malaysia, which began during Epidemiological Week (Ep Wk) 4 in 2020, to the last Ep Wk 18 in 2022. Data were aggregated by Ep Wk and analysed in terms of COVID-19 cases, deaths, ICU admissions, ventilator requirements, testing, incidence rate, death rate, case fatality rate (CFR) and test positivity rate by years (2020 and 2022) and for each outbreak of COVID-19.